PENGARUH MOTIF BERBELANJA (SHOPPING MOTIVES) DAN ATRIBUT TOKO (STORE ATTRIBUTES) TERHADAP KEPUTUSAN PEMBELIAN PADA HYPERMART SUN PLAZA MEDAN - johannes antonius manurung; marhayanie marhayanie (Jurnal Media Informasi Manajemen, 2013)
Abstract This study aims to determine the influence of shopping motives and store attributes to the purchasing decision in Hypermart Sun Plaza Medan. The population in this study were all customers Hypermart Sun Plaza Medan who has purchased decisions whose numbers are unknown. Sampling technique using a purposive sampling method. The analysis method used is descriptive analysis method and the multiple regression analysis method. This research is associative research, and data used are primary and secondary data obtained through the study of the measurement documentation and questionnaires using likert scale. The results of this study indicate that simultaneous shopping motives, and store attributes has positive and significant impact on purchase decisions Hypermart Sun Plaza Medan. Partially shopping motives can be seen that the variable is the most dominant variable influencing the purchase decision in Hypermart Sun Plaza Medan. Value Adjusted R Square = 0.266, mean 26,6% purchase decision factors can be explained by the independent variable (shopping motives and store attributes) while the remaining 73,4% is explained by other factors not examined in this study. Keywords: shopping motives, store attributes and purchasing decisions.